Poly-(lactic-co-glycolic acid) /poly-(vinyl alcohol) and cobalt ferrite magnetic nanoparticles as vanillin carriers. Issue 2 (3rd April 2023) - Naidek, Naiane; Khalil, Najeh Maissar; Almeida, Carlos Alberto Policiano
ABSTRACT: Besides being known by food and perfume industries, vanillin has also important pharmacological properties such as anti-inflammatory and antibacterial activities. The use of magnetic nanoparticles as carriers for a vanillin delivery system is a way to explore its benefits in human beings. In this paper, poly(lactic-co-glycolic acid) (PLGA) nanoparticles stabilized by poly(vinyl alcohol) (PVA) and containing magnetic CoFe2 O4 and vanillin have been prepared using a double emulsion-solvent evaporation method. The morphology, particle size, structure, and surface properties of the nanoparticles were investigated by transmission electron microscopy, zeta-potential measurements, X-ray diffractometry, Fourier transform infrared spectroscopy, magnetic hysteresis loops, and thermogravimetric analysis. The spherical nanoparticles presented negative charge, with zeta-potential values ranging from −9.15 to −5.64 mV, high thermal stability, superparamagnetic properties, and excellent encapsulation of the vanillin (around 80%). Accordingly, such PLGA/PVA nanoparticles encapsulating vanillin and CoFe2 O4 exhibited the desired features to suggest their potential use as drug delivery systems. Highlights: PLGA/PVA nanoparticles with CoFe2 O4 were synthesized for the targeted delivery of vanillin. The spherical nanoparticles presented negative zeta-potential ranging from −9.15 to −5.64 mV. Encapsulation promoted an increased release rate of vanillin. Analytical validation was used for vanillin quantification.